El secularismo saint-simoniano y la crisis de las sociedades tardo-modernas - Durán Vázquez, José Francisco (Nómadas. Critical Journal of Social and Juridical Science, 2008)
The present work tries to analyze Saint-Simon’s work as one of the first and more finished projects of building of a secular order articulated around the production and to the work, destined to replace the old man order estamental. From this perspective, the work saintsimoniana would complete the whole program of social reform of secular character on which the different currents of the socialism will rest, and of the one that will depart likewise Émile Durkheim’s thought, one of whose principal pretensions was, since it will be reminded, to fuse the socialism and the liberalism in a social doctrine that the new industrial society was legitimizing. Saint-Simon’s work will anticipate thus the content of the principal ideologies that the modern societies of market will sustain and legitimize. In her the key principles is present that will backbone to these societies, and from her it is also possible to understand and to interpret the consequences that there has had the establishment of the above mentioned order in the late-modernity. This one is precisely the purpose that chases the work that later one presents, whose first epigraphs will be dedicated when the ideas exposed directives of the thought saint-simoniano, for in the last part to show what has meant the accomplishment of this project for the joint of the modern societies, who sharpen her crisis at present under the inability to solve their problems without leaving of the ideological circle that they themselves have planned, and of which Saint-Simon’s work is one of his more out-standing examples.